Altered Expiratory Flow Dynamics at Peak Exercise in Adult Men With Well-Controlled Type 1 Diabetes - Hyrylä, Vesa V.; Rissanen, Antti-Pekka E.; Peltonen, Juha E.; Koponen, Anne S.; Tikkanen, Heikki O.; Tarvainen, Mika P. (Frontiers in Physiology, 2022)
Type 1 diabetes may, in time, cause lung dysfunction including airflow limitation. We hypothesized that ventilatory flow morphology during a cardiopulmonary exercise test (CPET) would be altered in adult men with well-controlled type 1 diabetes. Thirteen men with type 1 diabetes [glycated haemoglobin A1c 59 (9) mmol/mol or 7.5 (0.8) %, duration of diabetes 12 (9) years, and age 33.9 (6.6) years] without diagnosed diabetes-related complications and 13 healthy control men [age 37.2 (8.6) years] underwent CPET on a cycle ergometer (+40 W / 3 min until volitional task failure). We used a principal component analysis-based method to quantify ventilatory flow dynamics throughout the CPET protocol. Last minute of each increment, peak exercise, and recovery were examined using linear mixed models, which accounted relative peak oxygen uptake and minute ventilation. The type 1 diabetes participants had lower expiratory peak flow (P = 0.008) and attenuated slope from expiration onset to expiratory peak flow (P = 0.012) at peak exercise when compared with the healthy controls. Instead, during submaximal exercise and recovery, the type 1 diabetes participants possessed similar ventilatory flow dynamics to that of the healthy controls. In conclusion, men with well-controlled type 1 diabetes and without clinical evidence of diabetes-related complications exhibited attenuated expiratory flow at peak exercise independently of peak oxygen uptake and minute ventilation. This study demonstrates that acute exercise reveals alterations in ventilatory function in men with type 1 diabetes but not until peak exercise.